Performance of Row Cover with Mulch on Early Sowing of Watermelon in Semi-Arid Region - Prajapati, G. V.; Sojitra, M. A.; Cholera, S. P.; Jadav, B. K.; Chauhan, P. M. (International Journal of Economic Plants, 2024)
The experiment was conducted during the months of January to March in the year 2023 at Department of Renewable Energy Engineering, Junagadh Agricultural University, Junagadh (Gujarat). A field experiment was conducted to assess the performance of mulch and row covers in early watermelon cultivation with the primary aim on strategically removing row covers days after sowing. Randomized Block Design was employed with featuring of three treatments (mulching without row cover, mulching with row cover for 30 days and mulching with row cover for 45 days). Various yield and yield attribute parameters were recorded and analysed. The research findings indicated that the removal of row covers 30 days after sowing significantly influenced main vine length (2.72 m), number of nodes per main vine (36.40), number of fruits plant-1 (2.53), yield plant-1 (4.21 kg) and yield ha-1 (62.32 t ha-1). Removal of row covers 30 days after sowing exhibited higher net returns (Rs. 4, 85, 419 ha-1) and higher benefit-cost ratio (4.52). Removal of row cover 45 days after sowing significantly reduced the watermelon yield. The results unveiled that mulching with a row cover aster 30 days of sowing is the optimal approach for increasing watermelon yield and net returns in early watermelon cultivation.